Caracterización de residuos sólidos y efluentes (sangre) de vacunos generados en el Matadero Municipal de Punchana-2017 - Dávila Alva, Emerson (2024)
The work was carried out in Iquitos in the Municipal Slaughterhouse with the purpose of identifying the residuals generated by sacrifice of the bovine livestock, the rehearsal was explanatory evaluative, the design it was descriptive, like sample one had 28 mature animals (both sexes), processed the obtained data you concludes: The current Municipal slaughterhouse of the city doesn't have an appropriate handling of the generated organic residuals (hogwash and blood) and all this is discharged in the sewer system system after the benefit that is carried out to the animals, only counting a day of benefit (28 animals) one has a production effluent average (it bleeds) of 168.4 liters and a hogwash production (residuals in the stomach) of 197 kg, the one which if we multiply it for 30 days one would have a production of (5 052 liters and 5 910 kg respectively) these values analyzed annually would represent a discharge of (61 466 liters of blood and 71 905 hogwash kg), for what one can say that the activities of benefit and handling of these organic waste in the municipal slaughterhouse are not the appropriate ones.